Improving comprehensive genotyping in patients with newly diagnosed non-squamous NSCLC: Results from a prospective trial of a behavioral nudge intervention. Issue 28 (1st October 2022) - Aggarwal, Charu; Carpenter, Erica L.; Scholes, Dylan G.; Hwang, Wei-Ting; McWilliams, Tara; Singh, Aditi Puri; Sun, Lova; Kosteva, John A.; Costello, Michael Robert; Doucette, Abigail; Gabriel, Peter Edward; Roy, Megan; et al.
Abstract : 362 Background: Despite current guidelines, less than 50% of patients with metastatic (m) non-squamous (NSq) NSCLC undergo comprehensive molecular genotyping. At our institution, based on improved comprehensiveness of genotyping with use of concurrent tissue (T) and plasma (P) next generation sequencing (NGS), we designed an electronic medical record (EMR)-based nudge intervention to auto-generate an order for P NGS at the time of initial consultation, while T NGS was carried out reflexively based on institutional pathways. Methods: A prospective study was conducted at the Abramson Cancer Center and 2 community sites within the University of Pennsylvania Health System after IRB approval. A provider team-focused EMR-based nudge intervention was designed to order P NGS at the time of new patient consultation. Eligible patients for the nudge were identified using an EMR based checklist, that included 3 criteria i. newly diagnosed, ii. treatment naïve, iii. mNSq NSCLC. Results from the intervention period (4/2021-12/2021) were compared to baseline data from similar patients treated at our institution between 01/2019 and 03/2021. Categories of NCCN guideline recommended molecular genotyping were defined as: i) comprehensive: EGFR, ALK, BRAF, ROS1, MET, RET, NTRK testing, and ii) incomplete or no testing performed. The proportion of patients with comprehensive molecular genotyping prior to 1st-line therapy were compared in the pre- and post-intervention groups using the chi-square test. Results: 526 patients with mNSq NSCLC were included in this analysis: 381 in the pre-intervention cohort, 145 in the post-intervention cohort. After implementation of the EMR-based nudge, a higher proportion of patients underwent concurrent T+P testing resulting in improved comprehensive molecular genotyping. In addition, a greater proportion of patients had comprehensive genotyping available prior to 1st-line therapy in the post-intervention vs pre-intervention cohort (Table). Conclusions: Across 3 practice sites, a provider team-focused EMR-based nudge intervention was associated with a significantly higher proportion of patients with mNSq NSCLC undergoing comprehensive molecular genotyping, both overall and prior to 1st-line therapy. These findings demonstrate that behavioral, EMR-based nudges can promote guideline concordant diagnostic testing at both community and academic sites and should be studied further as a tool to improve rates of molecular testing in NSCLC.Characteristic Pre-intervention ( N = 381) Post-Intervention ( N = 145) Significance Female (%) 54.8% 53.8% NS Median age, years (range) 66 [22-93] 68 [40-90] NS Current/Former Smoker 75.6% 74.5% NS Tissue + Plasma NGS 262 (68.8%) 131 (90.3%) p< 0.00001 Comprehensive NGS 332 (87.1%) 143 (98.6%) p = 0.00007 Comprehensive NGS prior to 1L 291 (76.3%) 125 (86.2%) p = 0.013